Mechanisms of chronic heart failure development in end-stage renal disease patients on chronic hemodialysis - Malík, J; Tuka, V; Mokrejšová, M; Holaj, R; Tesar, V (Physiological research, 2009)
More than 50 % of end-stage renal disease (ESRD) patients treated by chronic hemodialysis die from cardiovascular diseases, including congestive heart failure (CHF). The incidence of CHF is rising in both general and ESRD population. However, the mechanisms, which lead to the development of CHF in dialyzed patients, differ considerably. First, there are several factors leading to increase of the left ventricular afterload: volume overload between dialyses, hypertension, increased arterial stiffness, anemia, vascular access flow (arteriovenous fistula) and sympathetic activation. Second, hypertension, left ventricular hypertrophy, anemia and frequently present coronary artery disease worsen myocardial oxygenation. The combination of these factors explains the high incidence of CHF in dialyzed patients and their roles are reviewed in this article.
Keywords: Renal Dialysis; Kidney Failure, Chronic; Humans; chronické selhání ledvin; dialýza ledvin; Heart Failure; lidé; srdeční selhání